2016
DOI: 10.2147/dddt.s114147
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant effects of isomeric nonimidazole histamine H<sub>3</sub> receptor antagonists

Abstract: Phenytoin (PHT), valproic acid, and modern antiepileptic drugs (AEDs), eg, remacemide, loreclezole, and safinamide, are only effective within a maximum of 70%–80% of epileptic patients, and in many cases the clinical use of AEDs is restricted by their side effects. Therefore, a continuous need remains to discover innovative chemical entities for the development of active and safer AEDs. Ligands targeting central histamine H3 receptors (H3Rs) for epilepsy might be a promising therapeutic approach. To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“… 10 , 11 , 13 16 , 30 , 31 The current was applied through ear electrodes for 1 s. Protection against the spread of MES-induced convulsion was defined as the abolition of the tonic hind limb extension (THLE) component of the convulsion. 10 , 11 , 13 , 15 , 32 , 33 The animals were divided into groups of eight mice. In the positive control group, mice were injected with VPA at a previously described dose of 300 mg/kg, this being the minimal dose of VPA that protected animals against the spread of MES-induced convulsions without mortality in mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 , 13 16 , 30 , 31 The current was applied through ear electrodes for 1 s. Protection against the spread of MES-induced convulsion was defined as the abolition of the tonic hind limb extension (THLE) component of the convulsion. 10 , 11 , 13 , 15 , 32 , 33 The animals were divided into groups of eight mice. In the positive control group, mice were injected with VPA at a previously described dose of 300 mg/kg, this being the minimal dose of VPA that protected animals against the spread of MES-induced convulsions without mortality in mice.…”
Section: Methodsmentioning
confidence: 99%
“… 10 12 Both major and minor malformations have been attributed to antiepileptic drugs (AEDs). 10 , 13 In addition, many epilepsy patients may also have cognitive problems in addition to suffering from seizures, 14 16 with the most common cognitive problem being memory deficit. 2 , 17 While the causes of reduced memory functions in patients with epilepsy have not yet been completely elucidated, the forms and frequencies of seizures and the side effects of AEDs at therapeutic doses have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The E159-provided procognitive effect was confirmed by conducting additional experiments in which the respective promising dose of E159 (2.5 mg/kg) and PYR (10 mg/kg), ZOL (10 mg/kg), SCO (1 mg/kg), or a combination of SCO and ZOL were co-injected. The doses of SCO, PYR, and ZOL were selected according to previous studies ( Orsetti et al, 2001 , 2002 ; Khan et al, 2015 ; Sadek et al, 2015 , 2016a , b , d ) ( Figures 2 – 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, evaluating numerous oxidative stress markers (e.g., malondialdehyde (MDA), glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD)) of PTZ-kindled animals were carried out to assess the effects of the novel H3R antagonist E177. Furthermore, and amongst all the brain regions, the hippocampus has gained attention in the PTZ model as it contains several distinct neuronal circuits related to seizure genesis [54][55][56][57][58][59]. In the present study, the capability of H3R antagonist E177 to attenuate oxidative stress markers was evaluated in hippocampus tissues of PTZ-kindled rats ( Figure 4A P < 0.05], respectively, and increased GSH levels, with [F (1,10) = 96.74; P < 0.001] and [F (1,10) = 356.1; P < 0.001], respectively, and as compared with PTZ-kindled rats.…”
Section: Effects Of E177 Treatment On Oxidative Stress Level Of Ptz-kmentioning
confidence: 99%
“…Moreover, chronic pretreatment of RAM to control rats also did not significantly alter oxidative stress statues, with [F ( Several preclinical studies revealed the potential memory-enhancing effect of numerous H3R antagonists [16,18,21,26,[55][56][57][58][59] capable of modulating the release of brain histamine (HA) by antagonizing H3 auto-receptors, and numerous other brain neurotransmitters, e.g., acetylcholine (ACh), γ-aminobutyric acid (GABA), and glutamate (GLU) by antagonizing H3 hetero-receptors in different brain regions [60][61][62].…”
Section: Effects Of E177 Treatment On Oxidative Stress Level Of Ptz-kmentioning
confidence: 99%